PSYCHOLOGICAL WELL-BEIN EDUKASI PROGRAM PSYCHOLOGICAL WELL-BEING SISWA UNTUK GURU BK SMP SIDOARJO: EDUKASI PROGRAM PSYCHOLOGICAL WELL-BEING SISWA UNTUK GURU BK SMP SIDOARJO - Muhammad Farid Ilhamuddin; Titin Indah Pratiwi; Bambang Dibyo Wiyono (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2023)
The developmental period of junior high school students has various kinds of dynamics, influences from colleagues, family environment and school environment. Some of the phenomena that occur are the emergence of anxiety, stress, depression and other mental disorders. Such conditions are common in junior high school students, so they need to be given education and understanding through counseling services so that they can be anticipated properly and reach the stages of development properly. Seeing these conditions, the counseling teacher needs to pay attention to the psychological aspects of students so that negative things don't happen, so they need to be given education about the importance of maintaining students' mental health. The concept of psychological well-being is one way out to provide students with an understanding of how important it is to have good mental health so that education about psychological well-being of students is felt to be important to be given to BK SMP teachers in Sidoarjo Keywords: Education, Psychological well-being, Guidance and Counseling Junior High School Teachers